Efficacy of an acceptance-based behavior therapy for generalized anxiety disorder: Evaluation in a randomized controlled trial - Roemer, Lizabeth (2008)
Generalized anxiety disorder (GAD) is a chronic anxiety disorder, associated with comorbidity and impairment in quality of life, for which improved psychosocial treatments are needed. GAD is also associated with reactivity to and avoidance of internal experiences. The current study examined the efficacy of an acceptance-based behavioral therapy, aimed at increasing acceptance of internal experiences and encouraging action in valued domains, for GAD. Clients were randomly assigned to immediate (n=15) or delayed (n=16) treatment. Acceptance-based behavior therapy led to statistically significant reductions in clinician-rated and self-reported GAD symptoms that were maintained at 3- and 9- month follow-up assessments; significant reductions in depressive symptoms were also observed. Seventy-eight percent of treated participants no longer met criteria for GAD and 77% achieved high end-state functioning at post-treatment assessment; these proportions stayed constant or increased over time. As predicted, treatment was associated with decreases in experiential avoidance and increases in mindfulness.